Encapsulation of Reactive Ti2AlC and Nb2AlC Particles via a Boehmite Precipitation Route. Issue 6 (27th February 2019) - Stumpf, Martin; Köllner, David; Biggemann, Jonas; Schüßler, Martina; Greil, Peter; Fey, Tobias
Abstract : Reactive Ti2 AlC and Nb2 AlC particles are encapsulated in a continuous boehmite shell by hydrolysis of ultrafine AlN powder in aqueous environment. The hydrolysis of AlN leads to the heterogeneous precipitation of nanolamellar boehmite on the surface of the M n  + 1 AX n phase particles after 24 h reaction time. The boehmite coatings completely cover the MAX phase particles (Nb2 AlC d 50  = 7.9 μm; Ti2 AlC d 50  = 9.6 μm) with a thickness of 200 nm (Nb2 AlC) and 135 nm (Ti2 AlC). The lamellar structure of the boehmite coating is maintained after calcination at 400 °C in air, resulting in coatings with a maximum surface area of 41 m 2  g −1 (Nb2 AlC) and 50 m 2  g −1 (Ti2 AlC). The stability of the coating is assessed by using the coated Nb2 AlC as particle filler in ZrO2 . The coating is stable after the spark plasma sintering process and covers complex features of the particles. The present work shows the feasibility to encapsulate reactive MAX particles with a continuous oxide shell. The coated particles can be used as ductile crack bridging or healing filler in reactive matrixes requiring a spatial separation between filler and matrix. Higher surface charges by Al–O bonds on the surface facilitate the dispersion of the carbide particles in aqueous slurries. Abstract : Ti2 AlC and Nb2 AlC particles are encapsulated in a continuous oxide shell by hydrolysis of ultrafine AlN powder. Zeta potential, particle size, and SEM/TEM micrographs reveal a continuous 135–200 nm thick boehmite coating on the particles. The investigation shows the feasibility to encapsulate MAX phase particles for use as ductile crack bridging or healing filler in reactive matrices.